2022
DOI: 10.3762/bjnano.13.123
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite–bioglass nanocomposites: Structural, mechanical, and biological aspects

Abstract: This research work focuses on the fabrication and study of a series of nanocomposites consisting of two types of hydroxyapatite (HA), obtained by precipitate (HAP) and sol–gel (HAG) methods, and a boro-silico-phosphate bioglass. The microstructure and chemical, mechanical, and biological properties as functions of three factors, namely (i) the type of hydroxyapatite, (ii) glass content, and (iii) sintering temperature, were investigated. It was found that all of these factors affect the final composition and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…50 Also, an adequate vascularization is essential to allow an appropriate bone healing process and VEGF is the main mediator during the process of angiogenesis and newly blood vessels formation. 22,[51][52][53] In the present study, a VEGF immunolabelling was observed for all treated animals. It has been reported that BG has a stimulatory effect on neovascularization by stimulating the secretion of angiogenic factors, 30,54 which, together with the osteopromotive properties of BG, might further influence bone formation.…”
Section: Discussionsupporting
confidence: 67%
“…50 Also, an adequate vascularization is essential to allow an appropriate bone healing process and VEGF is the main mediator during the process of angiogenesis and newly blood vessels formation. 22,[51][52][53] In the present study, a VEGF immunolabelling was observed for all treated animals. It has been reported that BG has a stimulatory effect on neovascularization by stimulating the secretion of angiogenic factors, 30,54 which, together with the osteopromotive properties of BG, might further influence bone formation.…”
Section: Discussionsupporting
confidence: 67%